Flexible, transparent and highly sensitive SERS substrates with cross-nanoporous structures for fast on-site detection. Issue 32 (30th May 2018) - Wang, Yingcheng; Jin, Yuanhao; Xiao, Xiaoyang; Zhang, Tianfu; Yang, Haitao; Zhao, Yudan; Wang, Jiaping; Jiang, Kaili; Fan, Shoushan; Li, Qunqing
Abstract : A flexible and transparent SERS substrate is fabricated on a PET film and fast, on-site and ultrasensitive SERS detection is realized. Abstract : A flexible and transparent film assembled from the cross-nanoporous structures of Au on PET (CNS of Au@PET) is developed as a versatile and effective SERS substrate for rapid, on-site trace analysis with high sensitivity. The fabrication of the CNS of Au can be achieved on a large scale at low cost by employing an etching process with super-aligned carbon nanotubes as a mask, followed by metal deposition. A strongly enhanced Raman signal with good uniformity can be obtained, which is attributed to the excitation of "hot spots" around the metal nanogaps and sharp edges. Using the CNS of Au@PET film as a SERS platform, real-time and on-site SERS detection of the food contaminant crystal violet (CV) is achieved, with a detection limit of CV solution on a tomato skin of 10 −7 M. Owing to its ability to efficiently extract trace analytes, the resulting substrate also achieves detection of 4-ATP contaminants and thiram pesticides by swabbing the skin of an apple. A SERS detection signal for 4-ATP has a relative standard deviation of less than 10%, revealing the excellent reproducibility of the substrate. The flexible, transparent and highly sensitive substrates fabricated using this simple and cost-effective strategy are promising for practical application in rapid, on-site SERS-based detection.